Anita - Vitale, Lito 1961- (Menemsha Films, 2012)
The story of a young woman with Down syndrome who lives a happy, routine life in Buenos Aires, being meticulously cared for by her mother Dora. One tragic morning in 1994, everything changes when Anita is left alone, confused and helpless after the nearby Argentine Israelite Mutual Association is bombed. As Anita wanders through the city, she learns not only to care for herself, but touches the lives of those around her, from an alcoholic to a family of Asian immigrants
Original: Argentinien 2009
Special features: Theatrical trailers
Bildformat 1.85:1
Keywords: People with mental disabilities / Drama; Down syndrome / Drama; Orphans / Argentina / Buenos Aires / Drama; Terrorism / Social aspects / Argentina / Buenos Aires / Drama; Jews / Argentina; Buenos Aires (Argentina) / Drama; Mongolismo / Teatro; Buenos Aires (Argentina) / Teatro; Down syndrome; Jews; Orphans; People with mental disabilities; Terrorism / Social aspects; Argentina; Argentina / Buenos Aires; Foreign films / Argentina; Motion pictures, Spanish; Feature films / Argentina; Foreign language films / Spanish; Motion pictures / Argentina; Spanish language films; Drama; Feature films; Fiction films; Video recordings for the hearing impaired; Materiales en español